2021
DOI: 10.5194/acp-2021-871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aqueous chemical bleaching of 4-nitrophenol brown carbon by hydroxyl radicals; products, mechanism and light absorptivity

Abstract: Abstract. The reaction of hydroxyl radicals (OH) with 4-nitrophenol (4-NP) in the aqueous solution was investigated at pH = 2 and 9. As a result, the molar yield of the phenolic products was measured to be 0.20 ± 0.05 at pH = 2 and 0.40 ± 0.1 at pH = 9. The yield of 4-nitrocatechol (4-NC) was higher at pH = 9; at the same time, a lower number of phenolic products was observed due to the hydrolysis and other irreversible reactions at pH > 7. Mineralization investigated with total organic carbon (TOC) techniq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…The steady-state concentration of OH in the aqueous phase ([OH] aq ) in the absence of organic reactants was approximately 6 × 10 −13 M, as estimated by fitting the measured rate of H 2 O 2 photolysis into a kinetic model. 61,62 This value is within the range of [OH] aq in atmospheric aqueous particles. 63,64 2.3.…”
Section: Aqueousmentioning
confidence: 99%
“…The steady-state concentration of OH in the aqueous phase ([OH] aq ) in the absence of organic reactants was approximately 6 × 10 −13 M, as estimated by fitting the measured rate of H 2 O 2 photolysis into a kinetic model. 61,62 This value is within the range of [OH] aq in atmospheric aqueous particles. 63,64 2.3.…”
Section: Aqueousmentioning
confidence: 99%
“…Phillips et al (2017) found that absorption increased 10% per pH unit in the range of 2-12, and the resulting change in the spectral shape caused the absorption Ångström exponent (AAE) to decrease by 0.18 per unit increase of pH. Besides, the time-scale of chemical bleaching of BrC chromophores was prolonged by a factor of 1.5-3 at pH = 2 or pH = 9 (Witkowski et al, 2021), and the formation of secondary BrC was even suppressed under pH < 2 (Kampf et al, 2012;Sedehi et al, 2013).…”
mentioning
confidence: 99%